ANALISIS SWOT DALAM RANGKA MENYUSUN STRATEGI KOMPETITIF PADA INDUSTRI KECIL ( STUDI KASUS IKM KERIPIK CUMI CIK NINA DIDESA BATURUSA KECAMATAN MERAWANG BANGKA INDUK) - Ari Sandria, Febryanti; Sitepu, H. Mimpin; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2020)
Conducted based on coaching data from April 2020 to June 2020. This research was carried out in the Baturusa Village, Merawang District, where there are Chips Squid Chips. Small and Medium Enterprises Squid Chips Cik Nina as an individual business that is well known in the area. A good business strategy is needed to deal with increasingly complex and competitive business competition. The method used in this research is qualitative and quantitative methods. Data collection techniques in research carried out by interview and then analyzed by SWOT. The type of data consists of primary and secondary data. The results of the research from the descriptive methodology of SWOT analysis can be obtained by the matrix value of internal factors 3.05 and the matrix value of external factors 2.70. This business is in cell number four (growth and build) so it is included in the growth strategy. Strategies suitable for this position are intensive strategies (market penetration, market development and product development) or integration (backward integration, forward integration and horizontal integration) can be the most appropriate for these divisions. The results of the SWOT analysis for the Small and Medium Enterprises in Cik Nina Calamari Chips in Baturusa Village, Merawang Regency are in quadrant I (one), namely an aggressive strategy). This strategy signifies a strong and capable company to continue to develop by taking opportunities or opportunities that exist to achieve maximum turnover. In this strategy, it can increase the competitiveness of small and medium sized Calamari Chips in Baturusa Village, Merawang District, Bangka Induk Regency.